Evaluation of pain on use of electrosurgery and diode lasers in the management of gingival hyperpigmentation: A comparative study - Shalu Chandna; Suresh Dyamappa Kedige (Wolters Kluwer Medknow Publications, 2015)
Background: Gingival depigmentation is a periodontal plastic surgical procedure whereby the gingival hyperpigmentation is removed by various techniques such as electrosurgery, cryosurgery, abrasion with diamond bur and lasers. The aim of this study was to determine the pain levels during the gingival depigmentation procedure using electrosurgery and lasers. Materials and Methods: Twenty patients, both male and female, between the ages of 20 and 40 years were randomly allocated into two groups of 10 patients each: Those undergoing depigmentation with electrosurgery (Group I) and those by diode lasers (Group II). Patients of both groups were asked to define the level of pain and discomfort by using the Visual Analog Scale (VAS) intraoperatively, 24 h post-operatively and 1 week post-operatively. Results: Both the groups showed a decrease in the pain levels, which was statistically highly significant 1 week post-operatively when compared 24 h post-operatively. There was a statistically highly significant difference in the pain levels between the electrosurgery and the lasers groups after 24 h (P < 0.001), with the lasers group demonstrating lesser pain and discomfort. Although there was no significant difference between the two groups intraoperatively and 1 week post-operatively on comparison, lesser mean scores were observed for the lasers group. Conclusion: The growing concern for esthetic requires the removal of hyperpigmentated gingival areas to create a confident and pleasant smile, which could be easily attained by using either electrosurgery or lasers. This study concluded that lasers produce lesser pain and discomfort compared with electrosurgery during gingival depigmentation.